Cohort study on 20 years’ experience of bilateral video- assisted thoracic sympathectomy (VATS) for treatment of hyperhidrosis in 2431 patients - Wolosker, Nelson; Campos, José Ribas Milanez de; Kauffman, Paulo; Silva, Marcelo Fiorelli Alexandrino da; Faustino, Carolina Brito; Tedde, Miguel Lia; Puech-Leão, Pedro; Pêgo Fernandes, Paulo Manuel (São Paulo Medical Journal, 2022)
BACKGROUND: Primary hyperhidrosis is a condition characterized by excessive sweating, inconsistent with the needs for thermoregulation. OBJECTIVE: To assess the effectiveness and the change in the quality of life of patients undergoing bilateral VATS (video-assisted thoracoscopic sympathectomy) for treatment of hyperhidrosis, in a large case series. DESIGN AND SETTING: Cohort study conducted in a tertiary hospital specializing in hyperhidrosis located in São Paulo, Brazil. METHODS: A total of 2,431 patients who underwent surgery consisting of bilateral video-assisted thoracoscopic sympathectomy between January 2000 and February 2017 were retrospectively assessed in an outpatient clinic specializing in hyperhidrosis. The patients underwent clinical and quality of lie assessments on two occasions: firstly, prior to surgery, and subsequently, one month after the operation. The presence or absence of compensatory hyperhidrosis (CH) and general satisfaction after the first postoperative month were also evaluated. RESULTS: All the patients operated had poor or very poor quality of life before surgery. In the postoperative period, an improvement in the quality of life was observed in more than 90% of the patients. Only 10.7% of the patients did not present CH, and severe CH occurred in 22.1% of the patients in this sample. CONCLUSIONS: Bilateral VATS is a therapeutic method that decreases the degree of sweating more than 90% of patients with palmar and axillary hyperhidrosis. It improves the quality of life for more than 90% of the patients, at the expense of development of CH in approximately 90% of the patients, but not intensely.